2014
DOI: 10.1038/ki.2013.546
|View full text |Cite
|
Sign up to set email alerts
|

Serum-soluble urokinase receptor levels do not distinguish focal segmental glomerulosclerosis from other causes of nephrotic syndrome in children

Abstract: In this prospective study, we measured serum levels of the soluble urokinase receptor (suPAR) in pediatric patients with nephrotic syndrome of various etiologies. Mean levels of suPAR were 3316 pg/ml in 99 patients with steroid-resistant focal segmental glomerulosclerosis and 3253 pg/ml in 117 patients with biopsy-proven minimal change disease, which were similar to that of 138 patients with steroid-sensitive nephrotic syndrome (3150 pg/ml) and 83 healthy controls (3021 pg/ml). Similar proportions of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 33 publications
2
68
0
1
Order By: Relevance
“…In addition, lower levels were associated with male sex and increased estimated GFR [38]. Findings in other cohorts have raised questions about the role of suPAR in the pathogenesis of proteinuria, its ability to discriminate FSGS from other forms of primary glomerular disease, and its predictive value in identifying recurrent disease post-transplant [39][40][41]. Additional studies are needed to determine the role of this specific molecule in primary FSGS in native kidneys and recurrent disease in renal allografts.…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition, lower levels were associated with male sex and increased estimated GFR [38]. Findings in other cohorts have raised questions about the role of suPAR in the pathogenesis of proteinuria, its ability to discriminate FSGS from other forms of primary glomerular disease, and its predictive value in identifying recurrent disease post-transplant [39][40][41]. Additional studies are needed to determine the role of this specific molecule in primary FSGS in native kidneys and recurrent disease in renal allografts.…”
Section: Pathogenesismentioning
confidence: 99%
“…In addition, circulating suPAR has been reported to positively associate with carotid atherosclerosis and increased cardiovascular risk in CKD (29,30), and is also reported to be involved in renal damage that might progress to CKD (31). suPAR was previously postulated to represent a specific biomarker for primary FSGS, but recently has been identified in other glomerular diseases and negatively correlated with GFR (23,30,32). In this study, the systemic level of suPAR in RVH was higher than observed in primary FSGS (approximately 4.6 ng/ml) (22,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the postulated central role and direct pathological action of suPAR in FSGS is debated intensively. Several studies report lack of differences in suPAR levels between FSGS and other kidney diseases and suggests rather a reduced glomerular filtration as a major cause of increased suPAR in patients with renal disorders [64][65][66][67][68][69]. suPAR is readily detected in both plasma and serum [50,70] and it is also found in urine [50], cerebrospinal fluid [71] and saliva [72].…”
Section: Supar As a Clinical Marker Of Inflammation And Organ Damagementioning
confidence: 99%